Peran Mediasi Dalam Alternatif Penyelesaian Sengketa Terhadap Sengketa Lingkungan Hidup Di Indonesia - A An Muzzamil Nur Illahi; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
Especially in environmental matters, mediation is a valuable alternative dispute resolution method. This procedure provides a more cooperative approach, emphasizing the search for solutions that benefit all parties. With the assistance of an impartial third party, mediation aims to help the disputing parties reach a mutually beneficial agreement. Mediation provides a more cost-effective and efficient resolution of environmental conflicts than litigation, which is often expensive and time-consuming. Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and the Supreme Court Regulation governing mediation procedures are two regulations that govern the mediation process. Flexibility, active participation of the parties, and the possibility of lasting results are some of the benefits of mediation.